Developing Prototype in Online Class using Justinmind: A COVID-19 Story - Noorihan Abdul Rahman; Rozianiwati Yusof; Nor Asma Mohd Zin; Zuriani Ahmad Zukarnain (Journal of Computing Research and Innovation, 2021)
COVID-19 gives a drastic change in our lifestyle. In education, it effects on motivation, routine and the dilemma in using certain application. The university has taken various proactive measures for ensuring the productivity of their stakeholders. Students and instructors are changing their teaching and learning style which this impact on learning technology usage while having online class. This paper shares COVID-19 story in terms of learning system development online which is challenging for learners and instructors. They need to adjust themselves so that the message is conveyed, and problem is solved during the online class. This paper looks at how the learners and instructors manage their online class by using an online prototype tool, Justinmind, for assisting them to learn system development during COVID-19. The learners have been asked to plan, gather, and design the user interface according to the requirements stated previously. This study found out that there are some difficulties in conducting system development class in online mode since there is a change of routine as well as teaching and learning style. However, the difficulties have been addressed by the utilization of the technology and thus creating more exciting journey for the class regardless of the pandemic era.